План-проект експозиційно-колекційної ділянки “Шипшини” - Klyuenko, O.V.; Klimenko, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The creation scheme of the expositional and collectional plot of rose’s species on the place of the old collection "Rosa L. species" is describes.